2020
DOI: 10.1142/s1793431120500165
|View full text |Cite
|
Sign up to set email alerts
|

Applying Adaptive Pushover Analysis to Estimate Incremental Dynamic Analysis Curve

Abstract: To estimate seismic demand and capacity of structures, it has been suggested by researchers that Incremental Dynamic Analysis (IDA) is one of the most accurate methods. Although this method shows the most accurate response of the structure, some problems, such as difficulty in modeling, time-consuming analysis and selection of the earthquake records, encourage researchers to find some ways to estimate the dynamic response of structures by using static nonlinear analysis. The simplicity of pushover analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Shoma Kitayama et al (Kitayama and Constantinou, 2019) employed Push over method to determine the collapse resistance of isolated structures. Through the study of different structural models, it is found that compared with the traditional push over method, the IDA method has higher accuracy in evaluating the seismic demand and capacity of the structure (Navideh et al, 2012;Ahmadi et al, 2020;Shafigh et al, 2021). On the basis of the IDA method, a vulnerability assessment of super high-rise structures is conducted, and a combined control scheme is developed to control the structural inter-story displacement (Zheng et al, 2015;He and Lu, 2019).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Shoma Kitayama et al (Kitayama and Constantinou, 2019) employed Push over method to determine the collapse resistance of isolated structures. Through the study of different structural models, it is found that compared with the traditional push over method, the IDA method has higher accuracy in evaluating the seismic demand and capacity of the structure (Navideh et al, 2012;Ahmadi et al, 2020;Shafigh et al, 2021). On the basis of the IDA method, a vulnerability assessment of super high-rise structures is conducted, and a combined control scheme is developed to control the structural inter-story displacement (Zheng et al, 2015;He and Lu, 2019).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…On the contrary, if the damage degree of spandrel exceeds that of pier, the failure mode is regarded as "strong pier and weak spandrel", which encourages spandrel to participate in the deformation and energy dissipation of masonry structures in advance [1,28]. Meanwhile, many theoretical analysis and experimental investigation have also been carried out [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of structural robustness usually is associated with the determination of the scope of structure, the structural modelling and analysis, the selection of the robustness index, and the calculation and evaluation of structural robustness. To properly understand the influence of structural performances on structural robustness, widely used methods related to structural modelling and analysis, e.g., analytical method, pushdown and pushover methods can be adopted [5][6][7]. Furthermore, the results of other research work, e.g., those related to shear-flexural interaction [8,9] will also be very helpful to improve the modelling accuracy and thereafter the accuracy of the robustness in the process of structural robustness assessment.…”
Section: Introductionmentioning
confidence: 99%